2021
DOI: 10.3390/molecules26020413
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Synthesis of Dicarboxylic Derivatives of Bis(pyrazol-1-yl)alkanes

Abstract: Carboxylation of bis(pyrazol-1-yl)alkanes by oxalyl chloride was studied. It was found that 4,4′-dicarboxylic derivatives of substrates with electron-donating methyl groups and short linkers (from one to three methylene groups) can be prepared using this method. Longer linkers lead to significantly lower product yields, which is probably due to instability of the intermediate acid chlorides that are initially formed in the reaction with oxalyl chloride. Thus, bis(pyrazol-1-yl)methane gave only monocarboxylic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The NMR data agree well with the data of very recently published dicarboxylic derivatives of bis ( pyrazol-1-yl)alkanes including a bis(4-carboxylpyrazol-1-yl) methane by A. S. Potapov and coworker. 17 The presence of non equivalent carboxylic acid functionalities was also supported by IR spectroscopy, as they give rise to vibrational bands at 1753 and 1676 cm −1 , respectively. Due to H 3 bcpza holding these two different types of carboxylic groups, two different pK a values are to be expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…The NMR data agree well with the data of very recently published dicarboxylic derivatives of bis ( pyrazol-1-yl)alkanes including a bis(4-carboxylpyrazol-1-yl) methane by A. S. Potapov and coworker. 17 The presence of non equivalent carboxylic acid functionalities was also supported by IR spectroscopy, as they give rise to vibrational bands at 1753 and 1676 cm −1 , respectively. Due to H 3 bcpza holding these two different types of carboxylic groups, two different pK a values are to be expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…Bis(pyrazol-1-yl)methane-4,4 -dicarboxylic acid (H 2 bpmdc) was synthesized as described previously [15] and recrystallized from water to give single crystals suitable for X-ray crystal structure determination.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed a universal approach for the synthesis of a new series of bis(pyrazol-1-yl)alkane-4,4 -dicarboxylic acids starting from the commercially available pyrazole-4-carboxylic acid [15]. Taking into account the potential of these compounds as supramolecular building block, biologically active substances, monomers for polyesters and polyamides, we have studied the crystal structure and supramolecular analysis of Nheterocyclic compound titled bis(pyrazol-1-yl)methane-4,4 -dicarboxylic acid (H 2 bpmdc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest activity in 1 µg/mL and 2 µg/mL on drug sensitive (DS) and multidrug-resistant (MDR) Mycobacterium tuberculosis strains, equal to the activity of the basic antitubercular drug rifampicin, was recorded for 2-amino-8-oxa-1,5-diazaspiro[4.5]dec-1-en-5-ium chloride [ 4 ]. Potapov et al described different approaches to the synthesis of dicarboxylic derivatives of bis(pyrazol-1-yl)alkanes which are interesting building blocks for metal-organic frameworks [ 5 ]. Svete et al reported on the synthesis of a series of 12 silica gel-bound enaminones and their Cu(II) complexes, which were used as suitable heterogeneous catalysts in [3+2] cycloadditions of 3-pyrazolidinone-derived azomethine imines to terminal ynones, for the regioselective synthesis of 6,7-dihydro-1 H ,5 H -pyrazolo[1,2- a ]pyrazoles [ 6 ].…”
mentioning
confidence: 99%